Peculiarities of Representation in Civil Proceedings - K. R. Rezvorovych (Bulletin of Kharkiv National University of Internal Affairs)
The thesis was devoted to the research of the peculiarities of representation in the civil process. The main objective of this thesis is the determination of the peculiarities of legal adjusting for the representation in the civil process. Methodological basis of the thesis consisted of such methods as: formal-logical, system analysis, dialectical and hermeneutical. The relevance of this thesis is evidenced in particular by there that was disclosed such facts as: the content of the institute of representation in civil law and civil process doctrine; the circle of persons who can be representatives in civil procedure. It was made a systematic analysis of the provisions of the Civil Procedure Code (CPC) of Ukraine on the subject of the implementation of the representation of individuals in civil proceedings. There were investigated the problems of restricting the circle of persons who can be representatives in civil proceedings. The analysis of standing and its confirmation by various persons who can carry out representation in civil proceedings was done. According to the results of the research, it was established that modern CPC of Ukraine does not determine the essence of relations between representatives and persons whose interests they realize. The mainstreaming and law-governing influence is mainly related to the legal personality of the representatives, their procedural status. It was also determined the range of duties and rights of representatives within the civil legal process. In addition, it was proved that the modern CPC of Ukraine is being introduced in the state, in fact, a monopoly on the representation of the parties by a lawyer in the courts, in the civil process, but leaves the possibility of realizing the relations of representation between an individual and another person who does not have the lawyer status, who ruled only in, such cold as, minor affairs. Thus, the practical significance of the conclusions reached was aimed primarily at the theoretical and methodological plane to continue the reform of the institution of representation in the civil process, as well as in the practical activities of representatives in the context of expanding the opportunities for individuals to exercise their procedure’s rights.